Local Public Investment Drivers in Peru - Jimenez, Alvaro (2020)
Around half of Peru’s public investment is made by local governments. Through the estimation of a dynamic panel data model for 1796 local governments between 2010 and 2018, we find that the most important drivers for local public investment are: (i) availability of funding sources, especially those associated to non-renewable natural resource revenues; (ii) variables associated with each local government’s capacity to plan, budget and execute public investment; and (iii)  political budget cycle effects, especially during the year following local elections. Furthermore, we extend our analysis by differentiating between local governments with reelected and non-reelected authorities, and by grouping local governments according to their economic size. Most of our results are shown to be robust across different specifications. Results from this paper can be used as a starting point to design mechanisms that make public investment more stable and predictable in a context where reelection banning can further deepen public investment’s fall.